Plant Metabolites Drive Different Responses in Caterpillars of Two Closely Related Helicoverpa Species - Sun, Longlong; Hou, Wenhua; Zhang, Jiajia; Dang, Yuli; Yang, Qiuyun; Zhao, Xincheng; Ma, Ying; Tang, Qingbo (Frontiers in Physiology, 2021)
The host acceptances of insects can be determined largely by detecting plant metabolites using insect taste. In the present study, we investigated the gustatory sensitivity and feeding behaviors of two closely related caterpillars, the generalist Helicoverpa armigera (Hübner) and the specialist H. assulta (Guenée), to different plant metabolites by using the single sensillum recording technique and the dual-choice assay, aiming to explore the contribution of plant metabolites to the difference of diet breadth between the two species. The results depicted that the feeding patterns of caterpillars for both plant primary and secondary metabolites were significantly different between the two Helicoverpa species. Fructose, glucose and proline stimulated feedings of the specialist H. assulta, while glucose and proline had no significant effect on the generalist H. armigera. Gossypol and tomatine, the secondary metabolites of host plants of the generalist H. armigera, elicited appetitive feedings of this insect species but drove aversive feedings of H. assulta. Nicotine and capsaicin elicited appetitive feedings of H. assulta, but drove aversive feedings of H. armigera. For the response of gustatory receptor neurons (GRNs) in the maxillary styloconic sensilla of caterpillars, each of the investigated primary metabolites induced similar responding patterns between the two Helicoverpa species. However, four secondary metabolites elicited different responding patterns of GRNs in the two species, which is consistent with the difference of feeding preferences to these compounds. In summary, our results of caterpillars’ performance to the plant metabolites could reflect the difference of diet breadth between the two Helicoverpa species. To our knowledge, this is the first report showing plant secondary metabolites could drive appetitive feedings in a generalist insect species, which gives new insights of underscoring the adaptation mechanism of herbivores to host plants.